Podoba Slovencev v leposlovnem opusu italijanskega tržaškega pisatelja Claudia Magrisa - Smotlak, Maja (Primerjalna književnost, 2016)
The paper analyses six key concepts (Yugoslavia, Fascism, Trieste, the Slovenian language, German identity, and (un)popular Slovenians) with which the Italian Triestine author Claudio Magris (born 1939) built his literary image of Slovenians. His writing is compared with contemporary Slovenian Triestine narrative prose (from 1980 to 2016).
Keywords: Magris, Claudio, 1939-; Trst; italijanska književnost; tržaška književnost; imagologija; Slovenci; Slovenes; fašizem